NOTICING: A FACTOR TO IMPROVE IRANIAN PRE-INTERMEDIATE EFL LEARNERS’ STRUCTURAL ACCURACY - Faezeh Nemati; Hamid Ashraf (University of Kuningan, 2013)
Abstract: The present study was conducted to investigate the effect of noticing, explicit focus on form on linguistic accuracy. To fulfill the purpose of the study, 44 Iranian pre-intermediate EFL learners of one of the language institutes were chosen by means of administering the KET homogeneity test. These learners were pretested through a structured interview to check their current accuracy level regarding the oral production of five structures. Based on the results of the pretest, two matched groups, one as the control group and the other as experimental group, were formed. Then, two groups were provided with tasks through listening about the target structures in the study. Of course, the experimental group underwent focus on form explicitly through noticing, while the control group was not provided with it. After twenty sessions of treatment, each ninety minutes, the two groups were post tested through another structured interview. The data obtained from instruments used in the present study indicated that the instructional treatment, noticing, had a significant effect on the acquisition of the target forms. The scores of the participants demonstrated that in experimental group outperformed the control group in terms of the average accuracy gains. Finally, it was concluded that explicit focus on form, noticing, can lead to higher accuracy in oral production in comparison to control groupKeywords: explicit focus on form, noticing, accuracy